Comparison of the Antibacterial Activity of Chelating Agents Using the Agar Diffusion Method - Jr., A. Hinton; Ingram, K.D. (International Journal of Poultry Science, 2010)
The agar diffusion assay was used to examine antibacterial activity of 2 metal chelators. Concentrations of 0-40 mM of ethylenediaminetetraacetic acid (EDTA) and ethylenediamine-N,N=-disuccinic acid (EDDS) were prepared in 1.0 M potassium hydroxide (KOH). The pH of the solutions was adjusted to 11.0 with citric acid and wells in agar media seeded with bacterial isolates were filled with the solutions. Agar plates were incubated at 35oC for 18-24 h and zones of inhibition around the agar wells were measured. Results indicated that 10 mM EDTA produced significant (p<0.05) zones of inhibition of Acinetobacter calcoaceticus, Enterococcus faecalis, Escherichia coli, Listeria monocytogenes, Pseudomonas aeruginosa and Staphylococcus simulans growth, while 20 mM of EDTA produced significant (p<0.05) zones of inhibition of Salmonella typhimurium. Increases in the concentration of EDTA added to agar wells generally produced significantly increases in the size of zones of inhibition. EDDS only inhibited growth of A. calcoaceticus and P. aeruginosa. Significant (p<0.05) zones of inhibition of both isolates were produced by 10 mM of EDDS and significantly larger zones were produced by higher concentrations of EDDS, although intrazonal growth of A. calcoaceticus was present in all zones of inhibition of this isolate. The addition of these chelators to formulations of sanitizers used in poultry processing may improve the ability of sanitizers to wash away microorganisms on processed carcasses, but findings from this study indicate that these chelators also possess antimicrobial activity that may aid in reducing contamination of carcasses.